2008
DOI: 10.1021/ja804580n
|View full text |Cite
|
Sign up to set email alerts
|

Oligo(N-aryl glycines): A New Twist on Structured Peptoids

Abstract: We explore strategies to enhance conformational ordering of N-substituted glycine peptoid oligomers. Peptoids bearing bulky N-alkyl side chains have previously been studied as important examples of biomimetic "foldamer" compounds, as they exhibit a capacity to populate helical structures featuring repeating cis-amide bonds. Substantial cis/trans amide bond isomerization, however, gives rise to conformational heterogeneity. Here, we report the use of N-aryl side chains as a tool to enforce the presence of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
252
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(270 citation statements)
references
References 76 publications
15
252
0
Order By: Relevance
“…Finally, the thioamide analog 15, like β-peptoid 12e, exhibited higher K cis/trans values than its oxoamide analog (13) in polar solvents, and a significant decrease in the cisamide fraction in CDCl 3 (Chart 1). This again indicates that there is an interaction between the sulfur and the aromatic residue, which results in favoring of the cis-amide conformation.…”
Section: −10mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the thioamide analog 15, like β-peptoid 12e, exhibited higher K cis/trans values than its oxoamide analog (13) in polar solvents, and a significant decrease in the cisamide fraction in CDCl 3 (Chart 1). This again indicates that there is an interaction between the sulfur and the aromatic residue, which results in favoring of the cis-amide conformation.…”
Section: −10mentioning
confidence: 99%
“…9,29 Finally, peptoid studies have also shown that direct attachment of a phenyl group to the nitrogen atom (i.e., prepared from aniline subunits) leads to a very strong preference for trans-amides. 13 A single β-peptoid model system of this type (5h) was evaluated and exhibited the expected selectivity, by virtually giving rise to single sets of signals in all tested solvents when analyzed by 1 H NMR. As mentioned, we also evaluated the entire series of side chains a−h in model systems having C-terminal amides (6a−6h) instead of esters, to mimic the environment of a β-peptoid residue within an oligomer more appropriately.…”
Section: −10mentioning
confidence: 99%
“…17 It has become clear that proteinpeptide interactions are very abundant in the cell and estimates suggest they represent 15-40% of all interactions, 18 making peptide discovery and development of wide applicability and interest. Cyclic peptides [19][20][21][22] and other modified peptides 23,24 can be highly potent as well as selective, providing a compromise between structural preorganization and sufficient flexibility to mold to a target surface and maximize binding interactions. There is much evidence that despite having molecular masses well above Lipinski's rule constraints, cyclic peptides and other macrocycles can possess drug-like physicochemical and pharmacokinetic properties such as good solubility, lipophilicity, metabolic stability and bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…For the N-aryl peptoid, local structure is controlled by incorporation of side chain groups that restrict the possible backbone conformational states through both steric and electronic effects. N-aryl side chains restrict the amide backbone nearly exclusively to the trans state (19) and the bulky iodo-and tert-butyl-substituents lead to additional biasing of the φ torsion (30). Unbranched N-alkyl side chains provide fewer local restrictions to the peptoid backbone (31), but can contribute to long-range interactions that can direct chain folding (12).…”
Section: Conformational Landscapes Of Foldable and Nonfoldable Peptoidmentioning
confidence: 99%
“…Such helices have been used to form tertiary assemblies (11, 16), and have been incorporated into enzymes with minimal loss of function (17). Alternatively, peptoid N-aryl side chains have been used to induce trans-amide helices that can mimic polyproline II structure (18,19). It remains to be determined how these local rules can be used to control the global three-dimensional structure of peptoid macromolecules (20).…”
mentioning
confidence: 99%